2007
DOI: 10.1177/00333549071220s215
|View full text |Cite
|
Sign up to set email alerts
|

Managing Chronic Hepatitis C in Primary-Care Settings: More than Antiviral Therapy

Abstract: Millions of Americans have chronic hepatitis C, which can cause cirrhosis, liver failure, and liver cancer. 1,2 Most scientific literature and educational materials discuss antiviral medications as if they are the only treatment for hepatitis C. Although antiviral medications may eradicate hepatitis C virus (HCV) infection, overemphasis of anti-HCV medications by pharmaceutical manufacturers and patient and health-care provider interest in curing the infection have contributed to the failure to recognize the b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 36 publications
2
12
0
Order By: Relevance
“…Several commentators have recommended that antiviral therapy can, and should, be delivered in the multidisciplinary primary care setting when focused on areas of high prevalence of HCV. 4,[8][9][10]15,17,[27][28] The findings of the current review have suggested that such primary care-based treatment is feasible with support from specialists. Such a model has treatment outcomes that are equivalent with secondary care services.…”
Section: Discussion Summarymentioning
confidence: 99%
See 2 more Smart Citations
“…Several commentators have recommended that antiviral therapy can, and should, be delivered in the multidisciplinary primary care setting when focused on areas of high prevalence of HCV. 4,[8][9][10]15,17,[27][28] The findings of the current review have suggested that such primary care-based treatment is feasible with support from specialists. Such a model has treatment outcomes that are equivalent with secondary care services.…”
Section: Discussion Summarymentioning
confidence: 99%
“…Furthermore, in the UK and US there are insufficient numbers of consultants and nurse specialists in infectious diseases, hepatology, and gastroenterology to cope with the enormous numbers of patients who have CHC. 4 The opportunity to treat hard-to-reach patients for CHC in prison has been recognised for several years. Skipper et al reported their evaluation of a prison outreach clinic in 2003, 5 concluding that there was an opportunity to treat patients, but low uptake and a large proportion of exclusions under the then-current guidelines meant the impact was limited.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is also likely that many people identified with positive anti-HCV test results in these settings will be uninsured or underinsured and thus unable to access medical evaluation and follow-up. 42,43 To meet these and future needs, U.S. policy makers will need to consider creating systems for training more health providers to deliver care for people with hepatitis C, 43 as well as funding and reimbursement systems modeled on or expanding such programs as the AIDS Education and Training Centers and Ryan White CARE Act. 49,50 Some promising initiatives from CDC and SAMHSA 24,28,29,37,44 are underway to promote the integration of adult hepatitis A and B vaccination and hepatitis C counseling and testing in STD, HIV, and other public health programs.…”
Section: Discussionmentioning
confidence: 99%
“…30,32,35 This supplement includes viewpoints and commentaries that address many of these barriers and challenges, including (1) access to and models for care of people identified with positive anti-HCV test results in the public sector; 42,43 (2) vaccination of high-risk adults; 29 and (3) data systems and other infrastructure barriers, such as categorical funding. 24,41 In addition, CDC describes progress in bringing together related prevention programs on a national level and promoting a comprehensive approach to prevention of HIV, STD, and viral hepatitis; 24 and the Substance Abuse and Mental Health Services Administration (SAMHSA) describes several new federal programs to advance integration of viral hepatitis prevention into drug treatment programs.…”
Section: Barriers and Challengesmentioning
confidence: 99%